(3QSGdI aj GdLhGH Yf GdCUhdI GdfUjQjIs - (3eMeO Hf EHQGgje Hf jMji GdbhGej GdTjQGRj, GdedG UOQ GdOjf,J (B1059 (3g` s
(3ChdgG (B:s
(3GdMeO GdefhQ GdfahS HCfhGQ GdYde hGdEjeGf hgGOj GdNdGFb HEQSGd GdQSd hEfRGd GdbQBf s
(3BNQgG (B:s
(3EdG HGdUhQI EdG Cf Hjf GdbHdJjf aQb HfjJ aj ehVYgG Je HYhf Gddg hMSf Jhajbg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B303 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B203s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdOcJhQ MSjf Ydj eMahX (B- (3HZOGO (B(195) s
Keywords: (3GdJhMjO hGdedd hGdfMds